2017
DOI: 10.15537/smj.2017.5.17965
|View full text |Cite
|
Sign up to set email alerts
|

Does pulmonary rehabilitation alleviate depression in older patients with chronic obstructive pulmonary disease

Abstract: Objectives:To identify if pulmonary rehabilitation can achieve a clinically significant alleviation in the level of depression among chronic obstructive pulmonary disease (COPD) patients older than 70 years.Methods:We conducted a retrospective secondary analysis of the patients’ electronic records from a major pulmonary rehabilitation center in Cleveland, OH, United States between 2010 and 2014. Profiles of 105 participants who had completed more than 6 pulmonary rehabilitation sessions and were older than 70 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 31 publications
(52 reference statements)
2
8
0
Order By: Relevance
“…In addition, PR may help reduce anxiety and depression. Our results revealed that depression and anxiety were significantly improved in the PR-based groups, especially in the high-intensity PR group, which is consistent with previous studies 3537…”
Section: Discussionsupporting
confidence: 93%
“…In addition, PR may help reduce anxiety and depression. Our results revealed that depression and anxiety were significantly improved in the PR-based groups, especially in the high-intensity PR group, which is consistent with previous studies 3537…”
Section: Discussionsupporting
confidence: 93%
“…Our results accord with a recent study showing that PR significantly reduced depression among patients with COPD. 38 A possible explanation for the absence of improvement in social isolation could be that patients with severe COPD are most likely to be environmentally limited by the need for oxygen therapy. 37,38 These may include worsening levels of functional exercise capacity, impaired quality of life, and increased depression and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…38 A possible explanation for the absence of improvement in social isolation could be that patients with severe COPD are most likely to be environmentally limited by the need for oxygen therapy. 37,38 These may include worsening levels of functional exercise capacity, impaired quality of life, and increased depression and anxiety. Thus, meticulous steps and effective strategies should be taken to encourage COPD patients to engage in social activities in the community and spend quality time with friends and families to combat loneliness and stigma.…”
Section: Discussionmentioning
confidence: 99%
“…Other data supporting the beneficial role of rehabilitation on depression and anxiety comes from the values measured by the Hamilton Rating Scale for Depression (HRSD) and the Hamilton Anxiety Scale (HAMA), the data they improve following intense activity and with patients with moderate and severe pathology [16]. The improvement of the emotional status increases the survival rates of the patient with COPD following training, even in people over 70 years of age, through the evaluation with the Beck Depression Inventory (BDI) [41].…”
Section: Effects Of Rehabilitation On Chronic Pain and On Emotional Statusmentioning
confidence: 99%
“…BT not only improves proprioceptive indices but could stimulate cerebellar areas to improve afference management body, which will be related to pain, depression, and anxiety. The pursuit of physical activity in the rehabilitation process improves motor coordination (and consequently proprioception), with improved emotional and pain threshold status [36,39,41]. Adding a specific stimulation for the cerebellar area (BT) could be a useful strategy for the implementation of the patient's well-being with COPD, to be combined with the usual rehabilitation process.…”
Section: The Proprioceptivity In Copd Patientsmentioning
confidence: 99%